2012
DOI: 10.1159/000341919
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analyses of Cerebrospinal Fluid Using iTRAQ in a Primate Model of Iron Deficiency Anemia

Abstract: Iron deficiency affects nearly 2 billion people worldwide, with pregnant women and young children being most severely impacted. Sustained anemia during the first year of life can cause cognitive, attention and motor deficits, which may persist despite iron supplementation. We conducted iTRAQ analyses on cerebrospinal fluid (CSF) from infant monkeys (Macaca mulatta) to identify differential protein expression associated with early iron deficiency. CSF was collected from 5 iron-sufficient and 8 iron-deficient an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 140 publications
0
20
0
Order By: Relevance
“…There is a large literature describing the negative consequences of early-life iron deficiency on both infant and adult learning and memory in humans [35,43]. Data from a non-human primate model suggests that abnormally patterned neural connectivity from early in life likely contributes to these abnormalities [33]. Our study may provide some of the specifically hippocampal cellular mechanisms for these observations.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…There is a large literature describing the negative consequences of early-life iron deficiency on both infant and adult learning and memory in humans [35,43]. Data from a non-human primate model suggests that abnormally patterned neural connectivity from early in life likely contributes to these abnormalities [33]. Our study may provide some of the specifically hippocampal cellular mechanisms for these observations.…”
Section: Discussionmentioning
confidence: 66%
“…A recent study in formerly iron deficient anemic monkeys indicates that these long-term functional changes relate to developmental alterations in proteins that are important for establishing and maintaining normal neuronal connectivity [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Failure to accumulate iron results in irreversible low iron levels in brain and associated motor, behavioral, and cognitive defects in adulthood, independent of improvement in peripheral hematological parameters in rodents and primates (56,57). Cognitive defects persisted in pups nursing from Hif-2α…”
Section: Discussionmentioning
confidence: 99%
“…A similar etiology of ID is also seen in human infants with rapid postnatal growth [24], particularly in those born with low iron stores [25]. Previous studies using this primate model of IDA have demonstrated altered CSF levels of several proteins using proteomic methods and abnormal levels of monoamine neurotransmitters (e.g., dopamine and norepinephrine) via HPLC analysis [2628]. These changes in critical proteins may also be indexed by changes in CNS metabolism that would reflect a more generalized disturbance in brain function in IDA.…”
Section: Introductionmentioning
confidence: 88%